Effects of regional anesthesia techniques on local anesthetic plasma levels and complications in carotid surgery: A randomized controlled pilot trial - Roessel, Thomas; Uhlig, Christopher; Pietsch, Joerg; Ludwig, Stefan; Koch, Thea; Richter, Torsten; Spieth, Peter Markus; Kersting, Stephan (BMC Anesthesiology, 2019)
Background: The ultrasound guided intermediate cervical plexus block with perivascular infiltration of the internal carotid artery (PVB) is a new technique for regional anesthesia in carotid endarterectomy (CEA). We conducted a pilot study investigating the effects of deep cervical block (DCB), intermediate cervical block alone (ICB) and PVB on perioperative complications in patients undergoing elective CEA. We hypothesized, that the ropivacaine plasma concentration is higher in patients receiving DCB compared to PVB and ICB. Methods: In a randomized controlled pilot study thirty patients scheduled for elective CEA were randomly assigned into three groups: DCB receiving 20 mL ropivacaine 0.5% (n = 10), ICB receiving 20 mL ropivacaine 0.5% (n = 10) and PVB receiving 20 mL ropivacaine 0.5% and 10 mL ropivacaine 0,3% (n = 10). As primary outcome, plasma levels of ropivacaine were measured with high performance liquid chromatography before, 5, 10, 20, 60, and 180 min after the injection of ropivacaine. Secondary outcomes were vascular and neurological complications as well as patients' and surgeons' satisfaction. All analyses were performed on an intention-to-treat basis. Statistical significance was accepted at p < 0.05. Results: No conversion to general anesthesia was necessary and we observed no signs of local anesthetic intoxication or accidental vascular puncture. Plasma concentration of ropivacaine was significantly higher in the DCB group compared to PVB and ICB (p < 0.001) and in the PVB group compared to ICB (p = 0.008). Surgeons' satisfaction was higher in the PVB group compared to ICB (p = 0.003) and patients' satisfaction was higher in the PVB group compared to ICB (p = 0.010) and DCB group (p = 0.029). Phrenic nerve paralysis was observed frequently in the DCB group (p < 0.05). None of these patients with hemi-diaphragmatic paralysis showed signs of respiratory distress. Conclusion: The ultrasound guided PVB is a safe and effective technique for CEA which is associated with lower plasma levels of local anesthetic than the standard DCB. Considering the low rate of complications in all types of regional anesthesia for CEA, larger randomized controlled trials are warranted to assess potential side effects among the blocks.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Carotid endarterectomy; Cervical plexus block; Local anesthetic; Plasma concentration; Regional anesthesia; Ropivacaine